Study on the characteristics of superconducting electrodynamic suspension system based on dynamic circuit theory. Issue 1 (4th January 2021) - Hu, Daoyu; Zhai, Maochun
Abstract : Purpose: The purpose of this paper is to analyze the influence of different parameters on the characteristics of the superconducting electrodynamic suspension (EDS) system. Design/methodology/approach: The authors used an analytical model based on the dynamic circuit theory to perform the analysis. The authors proposed an inductance criterion to improve the calculation accuracy. They also proposed a three-dimension finite element method (FEM) to verify the validity of the analytical model. Findings: The levitation force and guiding force increase with the superconducting magnet (SCM) speed and show a saturated trend, while the drag force decreases with the SCM speed. The vibration characteristic is the inherent characteristic of the superconducting EDS. The frequency and amplitude are affected by the gap between adjacent null-flux coils. The levitation force first increases and subsequently decreases with the levitation height. The total levitation force of the SCM increases with the superconducting coil (SC) number, while the average levitation force of an SC decreases with the SC number. The total levitation force nonlinearly increases with the SC number. Originality/value: The authors introduced an inductance criterion for better understanding and using the analytical model, and they also proposed a 3D FEM method. The 3D FEM method could be extended to simulate the other EDS systems with more complex structures which the numerical model is no longer applicable. The results of the parameter study could deepen people's understanding of EDS.